Sustainable Development in the Context of Corporate Governance: A Bibliometric Analysis (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This study aims to provide an overview of sustainable development and corporate governance research published in the Scopus database to track the development of scientific activities that could pave the way for future studies by highlighting gaps in this field. 506 studies in this field were identified, from 2002 to 2025, based on bibliometric analysis using VOSviewer. This paper highlights the prevailing trend of current research in the field of sustainable development and corporate governance by providing a detailed bibliometric analysis of the trend and development of research for the last ten years due to the increasing interest in sustainable development by companies in order to attract investments, which was also accompanied by an increase in the number of companies in their interest in corporate governance, including investigating countries, journals and keywords of research. The results indicate that researchers in the field of sustainable development and corporate governance converge in the interest of sustainable development and corporate governance between developing and developed countries. Through VOSviewer analysis, we found that the main reason for companies to disclose sustainable development is to attract investments and that corporate governance impacts on controlling and directing company management. The countries with the most publications and the most common keywords were selected. This paper provides evidence of the lack of interest of many companies in sustainable development in different countries. Finally, the data analysis identifies several potential research issues regarding the relationship between sustainable development and corporate governance, which serve as an area for future research. Once again, this study also provides a framework for companies to pay attention to areas related to sustainable development.